A Comprehensive Model Linking Human Resource Management Practices And Service-Oriented Organizational Citizenship Behaviors Of Customer-Contact Hotel Employees In Malaysia - Nasurdin, Aizzat Mohd.; Ahmad, Noor Hazlina; Tan, Cheng Ling (Universiti Sains Malaysia, 2015)
The two main objectives of this research are: first, to examine the direct effects of HRM practices (selective hiring, orientation, job security, training, compensation, performance appraisals, and career advancement) on service-oriented organizational citizenship behaviors and; second, to examine the in~lirect effects of HRM practices (selective hiring, orientation, job security, training, compensation, performance appraisals, and career advancement) on service-oriented organizational citizenship behaviors through the mediating effect of organizational commitment. Data was gathered from a sample of 580 customer-contact employees from 29 hotels in Peninsular Malaysia. Results using PLS technique revealed that selecte<ll HRM practices have direct as well as indirect effects on SO-OCBs via commitment. Findings, implications; limitations, and suggestions for future research are discussed.